Transcultural odyssey: from Chongqing to Singapore report - Zhao, Shiyuhan (Nanyang Technological University, 2024)
TRANSCULTURAL ODYSSEY: From Chongqing to Singapore is based on my personal experiences, representing a cross-cultural journey from my hometown, Chongqing, China, to an 8-year study in Singapore. The project aims to explore the cultural differences and difficulties that an international student faces by focusing on the rich interplay of customs, traditions, and daily practices that define life in both Chongqing and Singapore. In the end, the project aims to craft a personal odyssey, reflecting my unique journey and experiences.